Spol v slovenskih enojezičnih splošnih razlagalnih slovarjih kot slovnična in družbena kategorija - Ledinek, Nina (Slavistična revija, 2019)
The article discusses the category of gender in general monolingual explanatory dictionaries of Slovenian. Both the category of grammatical gender and the category of gender as a social phenomenon exert influence on the choice of data that are included in a lexicographic description and their structure in a dictionary entry. I emphasize the fact that the creation of dictionaries requires a high degree of social sensitivity, since users tend to perceive them as authoritative works reflecting the conceptual system of the language.
Keywords: gender (linguistics); lexicography; political correctness; politična korektnost; slovaropisje; Slovenian language; slovenščina; spol (jezikoslovje)